The Status of Curriculum Development and Implementation in Ethiopia Against Schwab’s Signs of Crisis in the Field of Curriculum - Mengistu, Mulualem; Melesse, Solomon; Melesse, Tadesse (Indonesian Journal of Curriculum and Educational Technology Studies, 2020)
The purpose of this paper is to analyze the status of curriculum development and implementation in the Ethiopian education system against Schwab’s Signs of Crisis in the Curriculum Field. Education policy documents of the Ministry of Ethiopia, different research journals, and experiences of the researchers were the major data sources in this study. Data were analyzed through narration-based on data driven themes. The analysis confirmed that Schwab’s sign of crises in the curriculum field were prevalent, and the resolutions made by the predominant view followers as a response to Schwab’s signs of crisis in the curriculum field were not in place in the curriculum development and implementation processes in the Ethiopian education system. It means that the curriculum field is still vague in the Ethiopian education system, which implies that the quality of education in Ethiopia is highly deteriorating. Finally, the researchers recommended that curricula specialists should exert unreserved effort to save the curriculum field from its gloomy occasion in the Ethiopian education system and thereby to assure renaissance for the quality of education. Abstrak Artikel ini bertujuan untuk menganalisis status pengembangan dan implementasi kurikulum dalam sistem pendidikan Etiopia mengacu pada rumusan krisis dalam bidang kurikulum oleh Schwab. Dokumen-dokumen kebijakan pendidikan yang dikeluarkan oleh kementerian Etiopia, jurnal-jurnal ilmiah, dan pengalaman peneliti menjadi sumber data utama penelitian ini. Data yang diperoleh dianalisis secara naratif berdasarkan tema-tema yang muncul. Analisis data menunjukkan bahwa rumusan kritis dalam bidang kurikulum yang dikemukakan oleh Schwab merupakan hal yang lazim dan resolusi yang dikemukakan oleh pandangan utama sebagai respons terhadap pandangan Schwab tersebut tidak diakomodasi dalam proses pengembangan dan implementasi kurikulum dalam sistem pendidikan di Etiopia. Hal tersebut menunjukkan bahwa bidang kurikulum di Etiopia masih tidak jelas dan berbuah pada kondisi pendidikan yang memburuk. Terakhir, peneliti merekomendasikan agar para ahli kurikulum dapat mengerahkan segala upayanya untuk menyelamatkan bidang kurikulum dari ketidakjelasannya dan dengan demikian dapat menjamin upaya kebangkitan kembali kualitas pendidikan di Etiopia.